Design and Performance Analysis of Silicon Photonic Waveguides for High-Speed Optical Communication - Sonali Gawali; Shravani Chavan; Sakshi Bhaganagare; Vaibhav Godase (International Journal of Optical Innovations & Research, 2025)
The exponential growth of data traffic in data centers and high-performance computing systems necessitates a paradigm shift from conventional electrical interconnects to high- speed, low-power on-chip optical interconnects. Silicon Photonics (SiP) is the leading platform for this transition due to its compatibility with CMOS manufacturing and the high- index contrast between silicon (Si) and silicon dioxide (SiO 2 ). This paper details the design, simulation, and comprehensive performance analysis of a single-mode silicon- on-insulator (SOI) rib waveguide specifically optimized for high-speed optical communication in the O and C bands (1500–1600 nm)[1-5]. The primary objective is to minimize propagation loss (α) and chromatic dispersion (D) while maintaining strong optical confinement. Finite-Difference Eigenmode (FDE) and Beam Propagation Method (BPM) simulations were employed to analyze key metrics: effective refractive index (n eff ), confinement factor, propagation loss, and Group Velocity Dispersion (GVD). The optimized rib waveguide, featuring a Si core height of 220 nm, width of 450 nm, and an etch depth of 120 nm, exhibits a simulated propagation loss as low as 0.22 dB/cm and a dispersion value of |D| .
Keywords: CMOS Photonics; Group Velocity Dispersion (GVD); High-Speed Communication; Optical Interconnects; Optical Waveguides; Propagation Loss; Rib Waveguide; Silicon Photonics